Water quality tests and behavioral factors of child diarrhoea in Dhaka slums - Alam, Mohammad Jahangir (BRAC University, 2010)
Diarrhoeal disease is one of the leading causes of morbidity and mortality in less developed countries, especially among children aged 0-5 years. It is a symptom of infection caused by a host of bacterial, viral and parasitic organisms most of which can be spread by contaminated water. Diarrhoea prevalence rate for the children in Dhaka slums is 214.29. The total costs of children's diarrhoea (adding all the direct and indirect) in Dhaka slums is Tk. 133.88 over a 15 day time interval. The water quality is measured at the point-of-use and the point-of-source by the total coliform, faecal coliform, and faecal streptococci tests per 100 ml water. The total coliform, faecal coliform, and faecal streptococci are at the point-of-source 651, 450, and 71 and at the point-of-use 919, 636, and 80 respectively. The test values at the point-of-use are greater than that at the point of- source due to drinking water contaminated by behavioral activities. Due to the almost perfect correlation between the total coliform, faecal coliform, faecal streptococci tests, we need to drop the values from these two tests (total coliform and faecal streptococci) in the econometric analysis. We will use the faecal coliform test, as it is the test most commonly referred to in the existing literature